Patients' medication reconciliation in a university hospital - Gabriella Fernandes Magalhães; Mário Borges Rosa; Lúcia Araújo Costa Beisl Noblat (Universidade de São Paulo, 2022)
Abstract Medication reconciliation is a strategy to minimize medication errors at the transition points of care. This study aimed to demonstrate the effectiveness of medication reconciliation in identifying and resolving drug discrepancies in the admission of adult patients to a university hospital. The study was carried out in a 300-bed large general public hospital, in which a reconciled list was created between drugs prescribed at admission and those used at pre-admission, adapting prescriptions from the pharmacotherapeutic guidelines of the hospital studied and the patients' clinical conditions. One hundred seven patients were included, of which 67,3% were women, with a mean age of 56 years. Two hundred twenty-nine discrepancies were found in 92 patients; of these, 21.4% were unintentional in 31.8% of patients. The pharmacist performed 49 interventions, and 47 were accepted. Medication omission was the highest occurrence (63.2%), followed by a different dose (24.5%). Thirteen (26.5%) of the 49 unintentional discrepancies included high-alert medications according to ISMP Brazil classification. Medication reconciliation emerges as an important opportunity for the review of pharmacotherapy at transition points of care, based on the high number of unintentional discrepancies identified and resolved. During the drug reconciliation process, the interventions prevented the drugs from being misused or omitted during the patient's hospitalization and possibly after discharge.